Pengeboran Batu Tambang Emas Tradisional Berisiko Terinfeksi Kuman Mycobacterium Tuberculosis (Studi Di Pertambangan Emas Tradisional Kabupaten Lebong, Bengkulu) - Darmawansyah Darmawansyah (Universitas Pekalongan, 2017)
Background: Pulmonary TB disease is a major cause of disability and death in most countries around the world. Pulmonary TB cases in traditional gold miners in Lebong District have increased. The purpose of the study is to prove the traditional gold mine drilling is at risk of infection with Mycobacterium Tuberculosis in Lebong District.Method: This study used case control design. The sample of this study were 78 people consisting of 39 cases and 39 controls on traditional gold miners. The independent variable of this research is mining drilling activity. The data were analyzed using chi square test and Odd Ratio along with Confidence Interval.Results: The statistical results revealed that there is a significant correlation of drilling mine activity to the incidence of pulmonary tuberculosis in traditional gold miners (p = 0.001). Mine rock drilling has a risk factor for the incidence of pulmonary TB in traditional gold miners (OR = 26.3 at 95% CI = 7,8-89,1). This means that miners engaged in rock drilling activities are 26.3 times more likely to suffer from pulmonary tuberculosis in traditional gold mining compared to miners who are not doing rock drilling activities.Conclusion: Performing traditional gold mining drilling activities is at risk of infection with Mycobacterium tuberculosis germs.Keywords: Drilling Activities of Mine Rock, Pulmonary TB, Traditional Goldmine Worker.